PENINGKATAN KEMAMPUAN BUM DESA MELALUI PELATIHAN MANAJEMEN PELAPORAN KEUANGAN BUM DESA DI KABUPATEN INDRAGIRI HULU, PROVINSI RIAU - Junita, Dewi; Triyani, Oetary; Hendriani, Sisi (Awal Bros Journal of Community Development, 2023)
One of the groundbreaking initiatives undertaken to stimulate and drive economic activities in rural areas is the establishment of Village-Owned Enterprises (BUM Desa). In the province of Riau, every village, totaling 1,591, has successfully established BUM Desa. Moreover, in the Indragiri Hulu Regency, there are currently 178 units of BUM Desa, categorized as pioneer (54 units), growing (88 units), developing (23 units), and advance (12 units). Despite these achievements, concerted efforts are imperative to further enhance the growth and progress of BUM Desa in Indragiri Hulu, including effective financial reporting management. The objective of the community development initiative is to provide knowledge through financial reporting management training for BUM Desa in the Indragiri Hulu Regency. To achieve this objective, the community development activities were implemented using various methods, including pre-tests, lectures, dialogues, and post-tests. The community development took place on October 24, 2023, in the Indragiri Hulu Regency, with 25 Operational Executives from 25 BUM Desa actively participating. The outcomes of this initiative demonstrated a heightened understanding among BUM Desa operational executives regarding Financial Reporting Management. This was achieved through comprehensive presentations, interactive discussions, and simulations facilitated by the community development team.